Clinical and genetic characteristics of pulmonary arterial hypertension in Lebanon - Ossama K. Abou Hassan; Wiam Haidar; Georges Nemer; Hadi Skouri; Fadi Haddad; Imad BouAkl (BMC, 2018)
Abstract Background Pulmonary arterial hypertension (PAH) is a rare disease with an incidence rate of 2-6 cases per million per year. Our knowledge of the disease in the Middle East and North Africa (MENA) region is limited by the small number of clinical studies and the complete absence of genetic studies. Methods Our aim was to shed light on the clinical and genetic characteristics of PAH in Lebanon and the region by using exome sequencing on PAH patients referred to the American University of Beirut Medical Center (AUBMC). Twenty-one idiopathic, hereditary and Congenital Heart Disease (CHD) PAH patients were prospectively recruited, their clinical data summarized, and sequencing performed. Results The mean age at diagnosis was 33 years with a female preponderance of 70%. The mean pulmonary artery pressure at the time of diagnosis was 55. Genetic testing showed that 5 out of 19 idiopathic and Congenital Heart Disease PAH patients had Bone Morphogenetic Protein Receptor 2 (BMPR2) mutations at 25% prevalence, with 2 of these patients exhibiting a novel mutation. It also showed the presence of 1 BMPR2 mutation with 100% penetrance in a heritable PAH family. In the remaining cases, the lack of a complete genotype/phenotype correlation entailed a multigenic inheritance; suspected interactions involved previously associated genes T-box transcription factor 4 (TBX4), Bone Morphogenic Protein 10 (BMP10) and Growth Differentiation Factor 2 (GDF2). Conclusions This is the first study that looks into the genetic causes of PAH, including known and new BMPR2 mutations, in the MENA region. It is also the first study to characterize the clinical features of the disease in Lebanon.